The predominance of Helicobacter pylori infection in children with abdominal cramping - Atif Amin, Baig; Muhammad Umer, Khan; Wajeeha, Tabassum (2019)
Helicobacter pylori (H. pylori) infection is a common problem in pediatric practice, and its acquisition is related to poor socioeconomic conditions. Although the organism is thought to be responsible for many diseases, it starts its symptoms from abdominal cramping and ultimately leads to gastric ulcer. The current research aimed to evaluate the occurrence of H. Pylori infection in children presented with abdominal cramping in a tertiary care setting at Lahore. The cross-sectional descriptive study was conducted at The Children Hospital and Institute of Child Health (CH & ICH) Lahore, Pakistan. In this study, 94 children of both genders were included. Blood samples were collected in a clotted gel vial after obtaining informed consent. Immunoassay method was used for the quantitative detection of IgG class antibodies. 49% of patients were positive for Anti H. PyloriIgG immunoglobulin. The H. pylori prevalence rate in females is more than that of males. Among positive patients, 15 (33%) males and 31(67%) females were affected. The results of the current study revealed that females are more infected by H. pylori than males. The statistical analysis obtained from the present study showed that the occurrence of Helicobacter pylori infection is the leading cause of recurrent abdominal discomfort in children.